2020
DOI: 10.1002/pc.25625
|View full text |Cite
|
Sign up to set email alerts
|

Development of graphite‐filled polymer blends for application in bipolar plates

Abstract: In this study, the potential of conductive polymer composites based on graphite‐filled polymer blend for achieving high‐performance polymer electrolyte membrane fuel cell (PEMFC) bipolar plates (BPs) was investigated. Maleic anhydride grafted polypropylene‐compatibilized polypropylene (PP)/epoxy blend was selected as the matrix due to its good combination of mechanical strength and ductility, and its potential to form a co‐continuous morphology, which promotes the selective distribution of the filler in one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 55 publications
1
25
0
Order By: Relevance
“…The maximum value of electrical conductivity recorded in this section was 21.7 S/cm at 84 wt.% graphite content. With an increase in the filler concentration, the interaction between the graphite microparticles has been increased, leaving behind a reduced polymer‐filler interface resulting in a significant enhancement in the electrical conductivity 32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum value of electrical conductivity recorded in this section was 21.7 S/cm at 84 wt.% graphite content. With an increase in the filler concentration, the interaction between the graphite microparticles has been increased, leaving behind a reduced polymer‐filler interface resulting in a significant enhancement in the electrical conductivity 32 …”
Section: Resultsmentioning
confidence: 99%
“…With an increase in the filler concentration, the interaction between the graphite microparticles has been increased, leaving behind a reduced polymer-filler interface resulting in a significant enhancement in the electrical conductivity. 32…”
Section: Effects Of Graphite Content On the Electrical Conductivitymentioning
confidence: 99%
“…All the plates exhibited a conductivity higher than 100 S cm −1 , significantly greater than the through-plane conductivities of some graphite−polymer composite plates previously reported in the literature. 21,22,27 The higher through-plane conductivity is attributed to the use of high-aspect-ratio graphite particles (cf. Figure 3b), the lower compression molding pressure (9.58 bar compared with 68.9 bar used by Huang et al 22 ) leading to a more random orientation and better interparticle contact of the conductive graphite flakes, and the higher graphite concentration in the plates of the present study (80−90 wt % compared with 64−70 wt % used in other graphite−polymer composites 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…No voltage and current values could be measured due to excessive flooding of the flow channels in the SiO 2 -coated bipolar plates. Alo et al 27 reported the synthesis of graphite bipolar plates using a maleic anhydride-grafted polypropylenecompatibilized polypropylene/epoxy blend as the matrix. They found that the plate with 80 wt % graphite exhibited the optimal combination of flexural strength and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 This can have significant influence on the behavior of their blend systems and cause blends of these polyolefins with the same polymer to exhibit considerably different properties. In our previous studies, 23,25,28 it was found that graphite-filled epoxy (PP/EP) and high-density polyethylene (HDPE/EP) blends (polyolefin: epoxy = 55:45) exhibited higher in-plane and through-plane electrical conductivities than several filled single polymers reported in the literature. Higher electrical performance of PP/EP and HDPE/EP composites was attributed to co-continuous structure of the blends, which favored concentration of filler in the epoxy, leading to more conducting pathways within the composites.…”
Section: Introductionmentioning
confidence: 98%